Cerebrovascular event secondary to illicit drug use - Sontay, Wilson (2024)
A 31-year-old woman, who was taking phentermine and metformin due to obesity, presented with left hemiparesis after ingesting alcohol, cocaine and marijuana. The CT scan showed an extensive cerebral infarction in the territory of the right middle cerebral artery and the angioresonance revealed total obstruction of this artery. Because of the time elapsed, thrombolysis was not attempted. With supportive measures and physiotherapy the patient improved in the following weeks.